The effects of frequent out-of-feed events on growth performance of nursery, growing, and finishing pigs - Linneen, S.K.; Goodband, Robert D.; Tokach, Michael D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
An “out-of-feed” event is defined as a period of time that pigs do not have access to feed as a result of late feed delivery (feeders running empty) or bridging of bulk bins, feed lines, or feeders. To determine the effects of these out-of-feed events on pig growth performance, nursery and growing-finishing pig studies were conducted. In Exp. 1, 190 pigs (initial wt 14.0 lb) were allotted to one of four experimental treatments. Treatments included a 20-hour feed withdrawal for 1, 2, or 3 randomly selected times during the 35-d trial or a control treatment in which feeders were never withdrawn. Feeders were withdrawn on d 11 for pigs with 1 out-of-feed event, d 8 and 23 for pigs with 2 out-of-feed events, and d 9, 14, and 20 for pigs with 3 out-of-feed events. Throughout the study, the week in which an out-of-feed event occurred, ADG and ADFI were decreased (P<0.06), compared with those of control pigs. In some instances, if the out-of-feed event occurred early in the week, pig growth performance was intermediate to that of control pigs and the other pigs with an out-of-feed event later in the week. In the following week, however, pigs that had an outof- feed event in the previous week had improved ADG and F/G, compared with performance of the others. For the overall study, there were no differences in growth performance among pigs with 0, 1, 2, or 3 out-of-feed events. In Exp. 2, 479 growing-finishing pigs were used in an 85-d trial in a commercial finishing barn to determine the effects of frequency and timing of out-of-feed events on pig performance. Treatments included feed withdrawal (20 h) weekly for the duration of the trial, feed withdrawn weekly from d 45 to 85 (market wt), or a control treatment in which pigs had access to feed for the duration of the trial. Feed withdrawal occurred on a randomly selected day, with the exception of Saturday, Sunday, or a day before a weigh day (usually a Wednesday every other week). There were no differences (P>0.13) in growth performance throughout the 85-d trial. With weekly out-of-feed events in the finishing phase, there is a possibility that pigs may quickly learn to adjust their feed intake for the out-of-feed event. In this study, however, results suggest that out-of-feed events (20 h or less) will have no long-term effects on growth performance in nursery or growing-finishing pigs.
Keywords: Finishing pigs; Feed management; Out-of-feed events; Starter pig; Swine